PERAN STAKEHOLDERS DALAM PEMANFAATAN INFORMASI GEOSPASIAL PADA PEMERINTAH DAERAH PROVINSI SUMATERA BARAT - adinda putri; Arie Yulfa (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
The aims of the study were 1) to find out the pattern of relationships between stakeholders and the Network Node Components in OPDs throughout West Sumatra Province, 2) to determine IDS readiness in OPDs throughout West Sumatra Province which were evaluated using Social Network Analysis with visualization of index diagrams. This type of research is a quantitative research with a survey method to OPDs throughout West Sumatra Province by distributing questionnaires. The data analysis technique in this study is Social Network Analysis which is used to calculate the centrality value which represents the role of each OPD in the availability of IDS to support Geospatial Information Network Nodes, especially in West Sumatra Province. The results of this study are 1) The BMCKTR and DISKOMINFO services are OPDs which are the center of centrality. By using Ucinet tools, it proves that the density in the network is above 50% so that the relationship is considered strong, 2) Based on the 13 OPDs that have been carefully examined, there are 3 OPDs that are not ready, 7 OPDs that are somewhat ready, and 3 OPDs that are quite ready.